IMPROVING OF EFFICIENCY OF BAND-BLOCK BRAKE WORK BY REDUCING OF DYNAMIC AND THERMAL LOADINGS - Kozak, F. V.; Krystopa, S. I.; Krystopa, L. I.; Arsenych, Y. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2018)
This article is devoted to theoretical and experimental research of loading of new multi-pair friction units of band-block brakes of drilling hoists of drill units in stand conditions. Mathematical dependencies are made to determine frictional forces, efforts of tensions of incident and matching branches of the tape and the brake moments developed by the internal and external friction pairs. On the basis of dynamic and thermal loading of the latter, rational structural parameters of the brake were determined.